THU0416 Disease Activity and Safety During Long-Term (104-Week) Treatment with Apremilast, An Oral Phosphodiesterase 4 Inhibitor, in Patients with Psoriatic Arthritis: Results from a Phase III, Randomized, Controlled Trial and Open-Label Extension (Palace 3). (9th June 2015) - Edwards, C.; Blanco, F.; Crowley, J.; Hu, C.; Shah, K.; Birbara, C.
Abstract : Background: Apremilast (APR), an oral phosphodiesterase 4 inhibitor, helps regulate immune responses in psoriatic arthritis (PsA). PALACE 3 compared the efficacy and safety of APR with placebo (PBO) in patients with active PsA, including active skin disease, despite prior conventional disease-modifying antirheumatic drugs (DMARDs) and/or biologics. Objectives: Evaluate the efficacy and safety of APR treatment over 104 weeks. Methods: Patients were randomized (1:1:1) to PBO, APR 20 mg BID (APR20), or APR 30 mg BID (APR30) stratified by baseline (BL) DMARD use (yes/no) and psoriasis involvement of <3% or ≥3% of the body surface area. Patients whose swollen/tender joint counts (SJC/TJC) had not improved ≥20% at Week 16 were considered non-responders and were required to be re-randomized (1:1) to APR20 or APR30 if initially randomized to PBO, or continued on their initial APR dose. At Week 24, all remaining PBO patients were re-randomized to APR20 or APR30. Double-blind APR treatment continued to Week 52; patients could continue APR for up to 4 additional years. Results: 505 patients were randomized and received ≥1 dose of study medication (PBO: n=169; APR20: n=169; APR30: n=167). Approximately 82% of randomized patients completing Week 52 were maintained on therapy in year 2. Patients taking APR demonstrated sustained decreases in disease activity at Week 104, with a mean change in DAS-28 (CRP) of -1.59 for patients receiving APR30 and -1.56 for patients receiving APR20 (Table ); 43.4% of patients receiving APR30 and 44.0% receiving APR20 achieved DAS-28 [CRP] remission at Week 104 (Table ). Sustained relief of signs and symptoms, as well as improvements in physical function, were also demonstrated by SJC/TJC mean percent change, HAQ-DI mean change, proportion of patients with HAQ-DI score exceeding the MCID ≥0.30 threshold, modified ACR20/ACR50/ACR70 response rates, and PASI-75/PASI-50 response rates (Table ). No new safety concerns were observed with treatment through Week 104, and long-term findings indicate that tolerability of APR improved with long-term exposure. During Weeks >52 to ≤104, adverse events (AEs) occurring in ≥5% of APR-exposed patients were nasopharyngitis and upper respiratory tract infection; most AEs were mild/moderate in severity. Serious AEs occurred in 6.2% (APR20) and 5.8% (APR30) during Weeks 0 to ≤52 and 7.5% (APR20) and 8.7% (APR30) over Weeks >52 to ≤104. Fewer discontinuations due to AEs occurred during Weeks >52 to ≤104 (3.5%) than during Weeks 0 to ≤52 (7.5%). Conclusions: Over 104 weeks, APR demonstrated sustained clinically meaningful improvements in PsA disease activity, physical function, and associated psoriasis. APR continued to demonstrate an acceptable safety profile and was generally well tolerated. Disclosure of Interest: C. Edwards Grant/research support from: Celgene Corporation, Pfizer Inc, Roche, and Samsung, Consultant for: Celgene Corporation, Pfizer Inc, Roche, and Samsung, Speakers bureau: Abbott, Glaxo-SmithKline, Pfizer Inc, and Roche, F. Blanco Consultant for: Bioiberica, Gebro Pharma, and Pfizer., J. Crowley Grant/research support from: AbbVie, Amgen, Celgene, Janssen, Merck, and Pfizer, Consultant for: AbbVie and Amgen, Speakers bureau: AbbVie, C. Hu Employee of: Celgene Corporation, K. Shah Employee of: Celgene Corporation, C. Birbara Grant/research support from: Amgen, Bristol-Myers Squibb, Incyte, Eli Lilly, Merck, and Pfizer Inc